Evaluating the role of manufacturing, retail, and agricultural value added in small medium enterprise RGDP growth in the Netherlands - Ergin Akalpler (Future Business Journal)
Abstract Purpose This study examines the impact of manufacturing value-added, retail trade, and value-added agriculture on the Real Gross Domestic Product of small and medium-sized enterprises in the Netherlands from 1970 to 2021. Design/methodology/approach The analysis utilizes stationary variables at level I(0) and applies the least squares method along with the Vector Autoregressive model. These methods focus on key variables critical to the Dutch economy, particularly the manufacturing sector, where many SMEs operate. Findings The study finds that a 1% increase in Manufacturing Value Added and Retail Trade leads to Real Gross Domestic Production growth of 35% and 30%, respectively, with strong correlations (0.80 for Manufacturing Value Added and 0.70 for Retail Trade) between these variables and Real Gross Domestic Production. The model’s high R-squared value (87.3%) suggests that Manufacturing Value Added and Retail Trade have long-term effects on Real Gross Domestic Production, while also influencing each other and Value Added Agriculture. Vector Autoregressive analysis further supports these findings, demonstrating Manufacturing Value Added’s substantial impact on Retail Trade and Value Added Agriculture. Additionally, the study identifies short-term effects, where Manufacturing Value Added and Retail Trade contribute significantly to Real Gross Domestic Production variations. Originality/value This study highlights the pivotal role of the manufacturing sector in driving economic growth by increasing product diversity and employment. Small and Medium Enterprises demonstrate faster growth and adaptability to new technologies than multinational corporations. Moreover, consumer demand for unique, Small Medium Enterprises-produced goods surpasses demand for mass-produced items from large companies, further emphasizing the value of Small and Medium Enterprises in the Dutch economy.